2016
DOI: 10.1101/gr.209536.116
|View full text |Cite
|
Sign up to set email alerts
|

Multiple major disease-associated clones ofLegionella pneumophilahave emerged recently and independently

Abstract: Legionella pneumophila is an environmental bacterium and the leading cause of Legionnaires’ disease. Just five sequence types (ST), from more than 2000 currently described, cause nearly half of disease cases in northwest Europe. Here, we report the sequence and analyses of 364 L. pneumophila genomes, including 337 from the five disease-associated STs and 27 representative of the species diversity. Phylogenetic analyses revealed that the five STs have independent origins within a highly diverse species. The num… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
113
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 78 publications
(130 citation statements)
references
References 47 publications
14
113
1
2
Order By: Relevance
“…For instance, all isolates belonging to the branch of the Paris strain are consistently transformable. This is concordant with the high rates or recombination observed in this ST1 lineage, with an average of nearly 10% of the genome of isolates originating from recombination (34). Similarly, all isolates of the ST47 cluster are consistently poorly transformable.…”
Section: Large Instraspecific Variations In Natural Transformability supporting
confidence: 73%
See 1 more Smart Citation
“…For instance, all isolates belonging to the branch of the Paris strain are consistently transformable. This is concordant with the high rates or recombination observed in this ST1 lineage, with an average of nearly 10% of the genome of isolates originating from recombination (34). Similarly, all isolates of the ST47 cluster are consistently poorly transformable.…”
Section: Large Instraspecific Variations In Natural Transformability supporting
confidence: 73%
“…Although conserved, the phenotype is not homogeneously distributed. The ST1 clade groups a majority of transformable isolates, consistent with high recombination rates observed in this clade (33,34). This contrasts with the absence of transformable isolates in the ST47 clade in which no recombination events could be detected (34).…”
Section: Discussionsupporting
confidence: 58%
“…Underwood et al also found that some isolates of the same ST (interestingly the close ST47) that were separated by several years and geographic location differed by just four SNPs [31]. The diversity could be different in other L. pneumophila lineages, however similar results have recently been shown in several other STs 1, 23, 36, 37, 47 and 62 [33,34]. …”
Section: Discussionmentioning
confidence: 88%
“…1B). Comparison of the Hfq amino acid sequence among more than 300 L. pneumophila strains sequenced in the last years (19, 2932) revealed that Hfq is 100% conserved across the different L. pneumophila strains. Analyses of four non- pneumophila Legionella species (33) showed that Hfq is 80% conserved (Fig.…”
Section: Resultsmentioning
confidence: 99%